Nanophotonic label-free biosensors for environmental monitoring. (June 2017) - Chocarro-Ruiz, Blanca; Fernández-Gavela, Adrián; Herranz, Sonia; Lechuga, Laura M
Graphical abstract: Highlights: We discuss the performance of different nanophotonic biosensors. We discuss the advantages that nanophotonic label-free biosensors confer over standard techniques. We present the most recent biosensing results for environmental monitoring. Abstract : The field of environmental monitoring has experienced a substantial progress in the last years but still the on-site control of contaminants is an elusive problem. In addition, the growing number of pollutant sources is accompanied by an increasing need of having efficient early warning systems. Several years ago biosensor devices emerged as promising environmental monitoring tools, but their level of miniaturization and their fully operation outside the laboratory prevented their use on-site. In the last period, nanophotonic biosensors based on evanescent sensing have emerged as an outstanding choice for portable point-of-care diagnosis thanks to their capability, among others, of miniaturization, multiplexing, label-free detection and integration in lab-on-chip platforms. This review covers the most relevant nanophotonic biosensors which have been proposed (including interferometric waveguides, grating-couplers, microcavity resonators, photonic crystals and localized surface plasmon resonance sensors) and their recent application for environmental surveillance.